Drawing Snow White and Animating Buzz Lightyear: Technological Toolkit Characteristics and Creativity in Cross-Disciplinary Teams - Mannucci, Pier Vittorio (Organization Science, 2017)
The use of technological tools to execute creative tasks is pervasive within cross-disciplinary teams, yet little attention has been paid to their role in influencing team creativity. In particular, no research has focused on how the characteristics of a team’s technological toolkit—the set of technological tools a team can draw upon to construct its actions—can affect team creativity. I propose that considering the toolkit, rather than just isolated tools, and the multiple functions played by tools is critical to understanding how technology characteristics influence team creativity. I hypothesize that creativity in cross-disciplinary teams is influenced by the size and field diffusion of the team toolkit, with size having a curvilinear relationship with creativity, and diffusion having a positive relationship. Moreover, I hypothesize that these effects will be attenuated when the number of team members who are experts with the focal tool is high. I test and find support for these hypotheses in a study set in the context of the Hollywood animation industry, a knowledge-intensive industry characterized by the presence of cross-disciplinary teams using a variety of technological tools. Theoretical and practical implications of the results are discussed.